Population Geography and Emergency Contraception Access in Louisiana - Elvira Chiccarelli; Nikka Khorsandi; S. Amanda Dumas; James K. Aden; Ryan H. Pasternak (MDPI AG, 2020)
We assessed the same-day availability of oral emergency contraception (EC) in five Louisiana communities, and evaluated this data for relationships between availability and local population demographics. Researchers called all retail pharmacies in five municipalities of varying sizes in order to inquire about the same-day stockage of EC products and their availability to teens. Individual pharmacies were then geolocated to a census tract, and call data was analyzed against neighborhood census data regarding population size, income, gender, race, family structure, and educational level. A multivariable logistic regression model was performed to predict the same-day availability of emergency contraception. EC was available on the same day in 66% of all pharmacies. The same-day availability of EC decreased with the local population size (p < 0.001), and the availability increased with higher levels of educational attainment (p = 0.0015). The largest census level predictor of access to same-day EC was the city population, with the availability increasing by 6.6% for every 10,000 person increase in population. Despite changing to over-the-counter sales in 2013, EC is still not widely available in all geographic areas. Its availability is partially predictable by local population demographics, and this difference may represent a health disparity for teens and women seeking EC.